Does the European Union achieve comprehensive blue growth? Progress of EU coastal states in the Baltic and North Sea, and the Atlantic Ocean against sustainable development Goal 14 - Wilfried Rickels; Christian Weigand; Patricia Grasse; Jörn Oliver Schmidt; Rüdiger Voss (Kiel Institute for the World Economy (IfW), 2018)
The Sustainable Development Goal for the oceans and coasts (SDG 14) as part of the 2030 Agenda can be considered as an important step towards achieving more comprehensive blue growth. Here, we selected a set of 18 indicators to measure progress against SDG 14 for EU coastal states in the Baltic and the North Sea and the Atlantic Ocean since 2012. In our assessment we distinguish between a concept of weak and strong sustainability, assuming high and low substitution possibilities, respectively. Overall, we show that the majority of countries in our assessment fail to achieve comprehensive blue growth. Sweden, Spain, Ireland, and in particular Portugal experienced a considerable reduction in scores since 2012. The only exemption is Estonia which managed to improve its scores over time under both concepts of sustainability. The unsustainable development at the EU level is mainly driven by deteriorations in indicators related to fisheries.
Keywords: Q01; Q22; Q56; 330; Sustainable Development Goals; Blue Growth; European Union; Fisheries